Energy evolution and damage constitutive model for deep marble under triaxial compression - Hou, Tingkai; Zhou, Zonghong; Zhang, Yonggang; Zhang, Jing (Frontiers in Earth Science, 2025)
IntroductionHigh ground stress in deep mining operations results in rocks exhibiting mechanical properties that differ from those at shallow depths. This study conducted conventional triaxial compression (CTC) tests to elucidate themechanical behaviors of deep marble under CTC conditions.MethodsInitially, it analyzed energy evolution of deep marble under CTC conditions and developed a damage variable (D) expression. Subsequently, we examined impacts of confining pressure (σ3) and D on dissipated energy (Wd) and Poisson’s ratio (μ′) and proposed an expression for damage energy dissipation rate (U). Finally, based on the first law of thermodynamics, we established a differential equation for energy balance that facilitated the development of a damage constitutive model (DCM) for marble under CTC conditions. This model effectively couples the internal energy and damage within the rock.ResultsThe results indicated that: (1) the maximum Wd increased with increasing σ3, and the Wd experienced stages of stability, slow growth, steady growth, and slowdown. (2) At a constant σ3, the μ′ under loading conditions increased with increasing damage level. However, as rock damage intensified in the residual stage, the growth rate of μ′ slowed and subsequently stabilized. (3) The proposed model effectively captures the nonlinear characteristics of stress-strain (SS) curves for deep marble under CTC conditions during the elastic, plastic yield, instability failure, and residual stages.DiscussionThis research offers theoretical insights for stability analysis in deep mining activities.